2010
DOI: 10.1016/j.aller.2010.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Delphi project in bronchial asthma. Two stages

Abstract: From the paediatric point of view, we have undertaken two Delphi studies into bronchial asthma. The first is related to the consensus known as the consensus document of the five associations. The second is more recent and has been undertaken with GEMA (the Spanish Guidelines on the Management of Asthma). The aim of this paper is to carry out a descriptive study comparing the 2 Delphi processes and to objectively assess if in some way behaviour over the past two years has changed as far as expert opinion is con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…21,22 The two main strengths of our study lie in the comprehensive systematic review of the literature and the participation of all those professionals involved in the care of paediatric asthma patients. For the most part, these professionals come from within the various regions of Spain and have different professional profiles, ranging from primary care to hospitals and pharmacies.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 The two main strengths of our study lie in the comprehensive systematic review of the literature and the participation of all those professionals involved in the care of paediatric asthma patients. For the most part, these professionals come from within the various regions of Spain and have different professional profiles, ranging from primary care to hospitals and pharmacies.…”
Section: Discussionmentioning
confidence: 99%
“…As far as the authors are aware, this is the first application of the Delphi exercise within a surgical service to rationalise follow‐up practices. The Delphi technique has previously been used to successfully facilitate consensus building amongst a group of experts within several medical fields 12–16 . Some of these experiences have been large Europe‐wide projects 15,16 .…”
Section: Discussionmentioning
confidence: 99%
“…The process was devised by Norman Dalkey and Olaf Helmer at the RAND Corporation in the 1950s [17] and draws its name from the Oracle at Delphi in Ancient Greece. Following the success of the method in business and military applications, the Delphi process is increasingly used in studies reported in the biomedical literature, with data suggesting that several hundred papers using this technique have been published [18] and has been applied in numerous initiatives in respiratory medicine [19,20,21,22]. …”
Section: Methodsmentioning
confidence: 99%